EFEKTIVITAS PEMBELAJARAN DI ERA NEW NORMAL TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH MATEMATIKA DISKRIT: Effectiveness of Discrete Mathematics Learning in New Normal Era on Student’s Learning Achievement - Usep Saepul Mustakim (Uniqbu Journal of Exact Sciences, 2020)
Learning in the new normal era during the co-19 pandemic will certainly be different from previous learning. Long before covid-19 learning was free to learn individually or in groups, but in this new normal era learning only focused on individuals without group assignments. So from that the purpose of this study is to find out how much the level of effectiveness of learning on student learning outcomes with high interpretation expectations. The method used in this study is a quantitative approach where data is obtained by statistical tests which are assisted with the application of SPSS for windows. The data is accumulated and analyzed by regression analysis so that after a statistical calculation is obtained a value of 73,2% in which a value of that size can be interpreted quite well or it can be said that learning is quite effective in the new normal era.